A man for all seasons : a play in two acts - Bolt, Robert (Vintage international, 1990)
The classic play about Sir Thomas More, the Lord chancellor who refused to compromise and was executed by Henry VIII. The story in play form of the conflict between Sir Thomas More & Henry VIII.